Pembrolizumab versus chemotherapy in recurrent, advanced urothelial cancer in Japanese patients: a subgroup analysis of the phase 3 KEYNOTE-045 trial - Nishiyama, Hiroyuki (Int J Clin Oncol, 2019)
BACKGROUND: The open-label, randomized, active-controlled KEYNOTE-045 study (NCT02256436) showed that second-line pembrolizumab significantly improved overall survival (OS) of patients with advanced/metastatic urothelial cancer (UC) that progressed after first-line platinum-containing chemotherapy, compared with standard chemotherapy (paclitaxel, docetaxel, or vinflunine). Pembrolizumab is approved for patients with bladder cancer in Japan. PATIENTS AND METHODS: Analysis was performed in the subgroup of Japanese patients enrolled in the KEYNOTE-045 study. Coprimary end points were OS and progression-free survival (PFS). Objective response rate (ORR) and safety were secondary end points. RESULTS: Fifty-two Japanese patients (pembrolizumab, n = 30; chemotherapy, n = 22) were followed up for a median of 26.1 months. Patients who received pembrolizumab compared with chemotherapy had a 19% lower risk for death (hazard ratio [HR] 0.81, 95% CI 0.44–1.50); after adjusting for baseline covariates, the HR for OS was 0.61 (95% CI 0.32–1.15). The 24-month OS rate was higher with pembrolizumab (26.9% vs 14.3%). PFS was 2.0 and 4.9 months for pembrolizumab and chemotherapy, respectively (HR 1.71, 95% CI 0.95–3.08). ORR was similar for pembrolizumab and chemotherapy (20.0% vs 18.2%); durability of response was higher with pembrolizumab: 67% and 33% of patients, respectively, maintained a response for > 12 months. Treatment-related adverse events, including grade 3–5 events, occurred less frequently with pembrolizumab. CONCLUSIONS: Pembrolizumab provided durable antitumor activity in patients with locally advanced/metastatic UC that progressed after platinum-containing chemotherapy in the overall population and in the Japanese subgroup; safety profile was consistent with that previously observed for pembrolizumab. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10147-019-01545-4) contains supplementary material, which is available to authorized users.